Laminated structure
The laminated structure with ultra-fine fibers and a base layer effectively absorbs low-frequency noise by resonating with sound waves, addressing the limitations of existing materials in vehicles.
Patent Information
- Application Number
- JP2023116419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Existing sound-absorbing materials struggle to effectively absorb low-frequency noise due to limitations in material thickness, which affects design and performance in vehicles, and existing laminated structures fail to provide sufficient sound absorption in low-frequency bands.
A laminated structure composed of an elaborate layer with ultra-fine fibers, oriented at angles of 0 to 45 degrees, and a base layer, where the elaborate layer is made of thermoplastic fibers with specific fiber diameters and densities, and optionally includes a porous layer to enhance sound absorption across a wide frequency range.
The laminated structure achieves excellent sound absorption characteristics in low-frequency bands by resonating with incident sound waves, providing stable and efficient noise reduction in vehicles.
Smart Images

Figure 2025014145000004 
Figure 2025014145000005 
Figure 2025014145000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated structure that is compatible with low frequency bands. [Background technology]
[0002] There is a great deal of interest in the indoor environment of automobiles and buildings, and in particular there is a high demand for quietness. For example, in the automobile field, it is necessary to deal with various noises such as engine noise, motor noise, wind noise, road noise, etc., and sound-absorbing materials are used to maintain quietness inside the vehicle.
[0003] In automobiles, noise countermeasures are implemented by incorporating or attaching sound-absorbing materials to parts inside the engine room, undercarriage, around the passenger compartment, etc. In recent years, with the spread of electric vehicles that do not have engines, the noise that requires countermeasures has shifted from high-frequency noise such as engine noise to low-frequency noise such as road noise, and there is a strong demand for improved sound-absorbing properties in the low-frequency range for vehicle sound-absorbing materials.
[0004] In sound-absorbing materials, the energy of the sound waves that enter the sound-absorbing material collides with or rubs against the constituent materials inside the sound-absorbing material, converting the energy of the sound waves into thermal energy, and the sound is absorbed by attenuating the energy of the sound waves. Based on this sound-absorbing mechanism, it is considered desirable for the structure of the sound-absorbing material to have a perforated structure through which sound waves can pass, and to have a large specific surface area inside the sound-absorbing material so that the viscous resistance experienced by the incident sound waves is large. Materials with a porous structure are generally used as such materials, and examples include glass wool, rock wool, foam, and nonwoven fabrics formed by entangling or bonding fibers.
[0005] In addition, in order to maximize the sound absorption characteristics of a porous sound absorbing material, it is necessary for the material thickness to correspond to the wavelength of the sound to be absorbed. Since high-frequency sounds have short wavelengths and low-frequency sounds have long wavelengths, the material thickness must be increased in order for the porous sound absorbing material to efficiently absorb low-frequency sounds. However, there is a limit to the material thickness depending on the application. For example, in the automotive field, a material thickness that exceeds the thickness of the car body is required to deal with low-frequency sounds such as road noise, but an increase in material thickness affects the design of the car and, further, leads to an increase in material weight, which may affect the driving performance such as a decrease in fuel efficiency of the car.
[0006] For this reason, various proposals have been made to achieve the requirements for improving the sound absorbing characteristics in the low frequency range and reducing the weight of sound absorbing materials.
[0007] For example, Patent Document 1 proposes a thin and lightweight sound-absorbing felt that is at least partially composed of a dense layer whose breathability and basis weight are adjusted within a certain range, and the dense layer is composed of ultrafine fibers.
[0008] Patent Document 2 proposes a sound-absorbing material in which the breathable skin material and breathable base material are composed of a structure including a fabric such as a nonwoven fabric, or a perforated film or foam sheet that has breathability, the breathable skin material is laminated on the breathable base material, and the airflow resistance per unit thickness of the breathable skin material is greater than the airflow resistance per unit thickness of the breathable base material.
[0009] Patent Document 3 proposes a laminated sound-absorbing material including a porous layer made of a fiber layer or a microporous membrane with a specified mean flow pore diameter and basis weight, and a base layer, in which the base layer is made of either a nonwoven fabric, a woven fabric, an expanded foam, or a honeycomb core, and is arranged so that the base layer is on the sound incident side and the porous layer is on the sound transmission side. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2017-37173 A [Patent Document 2] JP 2015-121631 A [Patent Document 3] JP 2020-19251 A Summary of the Invention [Problem to be solved by the invention]
[0011] The sound-absorbing felt described in Patent Document 1 has a dense layer on the surface, in which the air permeability and basis weight of felt made of entangled ultrafine fibers with a single fiber diameter of 1.0 μm or less and a fiber length of 20 to 150 mm are adjusted within a certain range, thereby increasing the specific surface area that can come into contact with sound waves, and the incident sound waves collide with and rub against the fibers that make up the felt, thereby exhibiting sound-absorbing properties. However, although it exhibits high sound absorption properties for sounds with a frequency of 1000 Hz, there are cases in which the sound-absorbing properties are insufficient in low frequency bands such as road noise, because it is a porous sound-absorbing material.
[0012] The sound-absorbing material described in Patent Document 2 exhibits excellent sound-absorbing performance in a wide frequency range, such as a high frequency range of 1000 Hz or more, by laminating a breathable skin material, the airflow resistance of which is 20 times or more and less than 2514 times the airflow resistance per unit thickness of the breathable base material, onto the breathable base material. However, since both the breathable skin material and the breathable base material are structures including nonwoven fabric, cloth, or breathable perforated film or foam sheet, and are porous materials, there are cases where the sound-absorbing properties are insufficient in low frequency ranges such as road noise.
[0013] The laminated sound-absorbing material described in Patent Document 3 has a porous layer made of a fiber layer or a microporous film laminated on a base layer, and specifies an average sound absorption coefficient measured from frequencies of 400 Hz to 1000 Hz. However, the embodiment uses a porous material, and the average sound absorption coefficient is only 0.40. Furthermore, in low frequency bands such as road noise, the sound absorption characteristics are sometimes insufficient.
[0014] Therefore, the present invention is intended to solve the above problems, and has an object to provide a laminated structure having excellent sound absorbing properties in the low frequency range. [Means for solving the problem]
[0015] In order to solve the above problems, the present invention has the following configuration. (1) A laminated structure in which a dense layer is laminated on a base layer, the dense layer having at least ultrafine fibers having a fiber diameter of 100 to 1000 nm, and a fiber orientation angle of the ultrafine fibers with respect to the planar direction of the dense layer is 0 to 45°. (2) The laminated structure according to (1) above, characterized in that at least one type of fiber among those constituting the dense layer has a flatness, which is the value obtained by dividing the length of the long axis of the fiber cross section by the length of the short axis, of 5 or more and an average length of the short axis of 1000 nm or less. (3) The laminated structure according to (1) or (2), wherein the dense layer is made of thermoplastic fibers. (4) The dense layer has a total areal density of 150 g / m 2 More than 1500g / m 2 The laminate structure according to (1) or (2) above, characterized in that: (5) The laminated structure according to (1) or (2) above, characterized in that a porous layer is laminated on the dense layer. Effect of the Invention
[0016] According to the present invention, a laminated structure having excellent sound absorbing properties, particularly in the low frequency range, can be obtained. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic diagram showing an example of a cross-sectional structure of a multi-layer laminated fiber used as a raw material for flat short fibers, which are an example of fibers constituting a dense layer of the present invention. [Diagram 2] 1 is a schematic diagram showing a cross-sectional structure of a flat short fiber, which is an example of a fiber constituting a dense layer of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] As a result of intensive research by the present inventors to achieve the above object, they found that in order to exhibit high sound absorption characteristics in the low frequency band of 1000 Hz or less, it is important for the sound absorbing material to have a resonance frequency that matches the frequency of the sound waves incident on the sound absorbing material. The sound absorption mechanism is presumed to be as follows. First, the sound waves incident on the sound absorbing material collide with the dense layer of the laminated structure of the present invention, causing the dense layer to vibrate. At this time, the frequency at which the vibration of the dense layer is maximized is determined by the structure of the dense layer and the structure of the base layer that plays the role of the air layer. It is presumed that when the frequency at which the vibration of the dense layer is maximized matches the frequency of the incident sound waves, that is, when they resonate, the laminated structure of the present invention exhibits high sound absorption characteristics. In order for the laminated structure of the present invention to absorb sound by the above sound absorption mechanism, it is necessary that the dense layer is laminated on the base layer.
[0019] The dense layer of the laminated structure of the present invention contains at least ultrafine fibers having a fiber diameter of 100 nm or more and 1000 nm or less. The fiber diameter here refers to a value determined by the method described in the Examples below.
[0020] When the fiber diameter of the ultrafine fibers is 100 nm or more, sound absorption properties are exhibited due to resonance between sound waves incident on the laminated structure and the vibration frequency of the dense layer. On the other hand, when the fiber diameter is 1000 nm or less, the packing density of the fibers constituting the dense layer is increased, and the dense layer is more likely to vibrate due to sound waves incident on the laminated structure, and sound absorption properties are exhibited due to resonance with the vibration frequency of the dense layer.
[0021] Among the fibers constituting the dense layer of the laminated structure of the present invention, the ultrafine fibers have a fiber orientation degree of 0 to 45° with respect to the planar direction of the dense layer. The fiber orientation degree here is a value obtained by the method described in the Examples below. The fiber orientation degree of the ultrafine fibers indicates the angle at which the fiber axis of the ultrafine fibers is oriented with respect to the planar direction of the dense layer, and the angle is expressed as 0 to 90°. The closer this angle is to 0°, that is, the more the ultrafine fibers are oriented in the planar direction of the dense layer, the more efficiently the sound waves incident on the laminated structure collide with the ultrafine fibers, and the dense layer vibrates. Therefore, if the fiber orientation angle of the ultrafine fibers is 45° or less with respect to the dense layer, the sound waves incident on the laminated structure will sufficiently collide with the ultrafine fibers, and the dense layer will vibrate. In order to more efficiently collide the sound waves incident on the laminated structure with the ultrafine fibers, the fiber orientation angle is preferably 30° or less. The substantial lower limit of the fiber orientation degree is 0°, at which the ultrafine fibers are completely oriented with respect to the planar direction of the dense layer.
[0022] Of the fibers constituting the dense layer of the laminated structure of the present invention, the ultrafine fibers preferably have a standard deviation of the fiber orientation degree of 0 to 20°. If the standard deviation is 20° or less, the ultrafine fibers are sufficiently oriented, so that sound waves incident on the laminated structure can collide with the ultrafine fibers more efficiently, which is preferable.
[0023] At least one type of fiber constituting the dense layer of the laminated structure of the present invention is preferably a flat fiber having a flatness of 5 or more, the value obtained by dividing the length of the long axis of the fiber cross section by the length of the short axis, and an average short axis length of 1000 nm or less. The flat fiber referred to here means a fiber having a flat fiber cross section, and the flat shape means a shape in which the long axis length and the short axis length are different, such as a rectangle or an ellipse. The degree of flatness is defined as the flatness, which is the value obtained by dividing the length of the long axis by the length of the short axis. The flatness in the present invention is a value determined by the method described in the Examples below. If the flatness is 5 or more, the bending rigidity in the minor axis direction and the major axis direction will be significantly different due to the morphological characteristics of the cross section, i.e., the shape anisotropy of the cross section, and the bending direction will be limited to the minor axis direction in the process of producing the dense layer, making it difficult to bend within the dense layer, which is preferable. In addition, the major axis is aligned in the planar direction of the dense layer, and many parts of the fiber surface are exposed on the surface layer of the dense layer, which is preferable because sound waves incident on the laminated structure will efficiently collide with the fibers. The flatness is more preferably 15 or more.
[0024] The fibers constituting the dense layer of the laminated structure of the present invention preferably have a fiber length of 0.1 mm or more and 10 mm or less. When the fiber length is 0.1 mm or more, the ultrafine fibers constituting the dense layer are sufficiently entangled with each other, and the fall-off of the ultrafine fibers can be suppressed. In addition, since the form of the dense layer is stable, the structure of the dense layer is less likely to change over time, and the sound absorption characteristics can be stably expressed. More preferably, it is 0.5 mm or more. In addition, when the fiber length is 10 mm or less, it is possible to prevent the ultrafine fibers from entangling alone to form fiber masses, which can disrupt the structure of the dense layer. Therefore, the vibration frequency of the dense layer is stable, and the sound absorption characteristics due to resonance are stably expressed. More preferably, it is 5 mm or less.
[0025] In the dense layer of the laminated structure of the present invention, the mixing ratio by fiber weight of each fiber is preferably 2.5% by weight or more and 70% by weight or less for ultrafine fibers and 30% by weight or more and 97.5% by weight or less for other fibers having a fiber diameter larger than that of the ultrafine fibers, in order to ensure the stable formation of microspaces and the strength of the dense layer.
[0026] In addition, the dense layer of the laminated structure of the present invention may contain binder fibers for the purpose of improving the strength and suppressing the falling off of the constituent fibers. In the present invention, a binder fiber mixing ratio of 5% by mass or more is preferable because it enables the fibers constituting the dense layer to be physically bonded to each other, increases the rigidity of the dense layer, and makes it easier for the dense layer to vibrate, thereby exhibiting high sound absorption properties. Furthermore, since the strength is improved, a laminated structure with excellent moldability and handleability can be obtained. In addition, based on the sound absorption mechanism of the laminated structure of the present invention, it is necessary to form fine spaces in the dense layer that cause a flow of fluid such as air inside the dense layer, and if this idea is pursued, the upper limit of the binder fiber mixing ratio is 75% by mass or less.
[0027] The binder fiber in the present invention is preferably a thermally adhesive binder fiber. After the thermally adhesive binder fiber is mixed to form a dense layer, the binder fiber is thermally bonded to the adherend by a drying process such as a Yankee dryer or an air-through dryer, or a heat treatment process such as a calendar. This thermal adhesion can increase the rigidity of the dense layer. An example of such a thermally adhesive binder fiber is a core-sheath composite fiber in which a polymer having a melting point of 150°C or less is arranged in the sheath. In this case, the core component fiber remaining after thermal adhesion can ensure the strength of the dense layer or play a role as a scaffold depending on its fiber diameter. Note that if the melting point of the core component of the binder fiber is higher than that of the sheath component and the melting point difference is 20°C or more, the sheath component on the binder fiber surface is sufficiently melted and the degree of decrease in the orientation of the core component is suppressed, so that sufficient thermal adhesion and high rigidity can be obtained. Another example of a thermally adhesive binder fiber is a fiber with a low crystallinity. When the degree of crystallinity is low, the amorphous regions are less likely to be hindered by the gliding regions when heated above the glass transition temperature, and can soften and flow sufficiently, so that they penetrate between the adherends during the heat treatment process and exhibit high thermal adhesion. Binder fibers with a low degree of crystallinity are also preferably ones with a flat fiber cross section. A flat fiber cross section increases the specific surface area compared to a circular fiber cross section, which increases the bonding area and is preferable because it can firmly and uniformly bond the adherends and exhibit excellent mechanical properties.
[0028] The fibers constituting the dense layer of the laminated structure of the present invention are preferably thermoplastic fibers from the viewpoint of manufacturing and waste treatment.The raw materials of the thermoplastic fibers may be those used for general synthetic fibers, such as aromatic polyesters represented by polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, etc., aliphatic polyesters represented by polylactic acid, aliphatic polyamides represented by polycapramide and polyhexamethylene adipamide, semi-aromatic polyamides represented by polyhexamethylene terephthalamide, thermoplastic elastomers represented by thermoplastic polyurethane, and polyolefins represented by polypropylene.In general, it is preferable to use aromatic polyesters or aliphatic polyamides from the viewpoint of mechanical properties, heat resistance, and handling during manufacturing.
[0029] The aromatic polyester is a high molecular weight substance having a repeating unit linked via an ester bond to a main chain consisting of a combination of an aromatic dicarboxylic acid and an aliphatic diol, an aliphatic dicarboxylic acid and an aromatic diol, or an aromatic dicarboxylic acid and an aromatic diol. Preferably, the aromatic polyester is made of an aromatic dicarboxylic acid and an aliphatic diol. Examples of such aromatic dicarboxylic acids include, but are not limited to, terephthalic acid, isophthalic acid, phthalic acid, 5-sodium sulfoisophthalic acid, 5-(tetraalkyl)phosphonium sulfoisophthalic acid, 4,4'-diphenyldicarboxylic acid, and 2,6-naphthalenedicarboxylic acid. Examples of such aliphatic diols include, but are not limited to, ethylene glycol, 1,3-propanediol, 1,4-butanediol, hexanediol, cyclohexanediol, diethylene glycol, hexamethylene glycol, and neopentyl glycol.
[0030] The aliphatic polyamide is a high molecular weight substance having a repeating unit in which a so-called hydrocarbon group is linked to the main chain via an amide bond. In general, it is synthesized by a polycondensation reaction using aminocarboxylic acid or cyclic amide as raw materials, or a polycondensation reaction using dicarboxylic acid and diamine as raw materials. Examples of such polyamides include polycapramide, polyundecanolactam, polylauryllactam, polyhexamethylene adipamide, polyhexamethylene sebacamide, polyhexamethylene dodecanediamide, etc.
[0031] The method for producing the polymer in the present invention is not limited, and the polymer may be produced by synthesis using a general polycondensation reaction, addition polymerization reaction, etc. Furthermore, when the raw materials used in production are collectively referred to as monomers, the raw materials include, but are not limited to, petroleum-derived monomers, biomass-derived monomers, mixtures of petroleum-derived monomers and biomass-derived monomers, and recycled monomers obtained by reusing polymers as raw materials using a chemical recycling method. Alternatively, the polymer may be produced from waste materials such as waste plastics using a material recycling method. Furthermore, the polymer in the present invention may be copolymerized or mixed with a second or third component in addition to the main component, as long as it does not deviate from the purpose of the present invention.
[0032] The laminated structure of the present invention may have a dense layer of two or more layers. As described above, the dense layer of the laminated structure of the present invention vibrates at a specific frequency, thereby exhibiting sound absorption characteristics for sounds having a frequency that resonates with the vibration frequency. If the vibration frequency is single, the dense layer exhibits high sound absorption characteristics for a specific sound that resonates with the vibration frequency, but the sound absorption characteristics are reduced for sounds that are slightly different in frequency from the vibration frequency other than the specific sound. However, when the dense layer is composed of two or more layers, in addition to the vibration of each layer, multiple layers can be combined to vibrate as a pseudo-single composite layer, and even if the thickness is thin, the peak of the vibration frequency becomes wide, and sound absorption characteristics can be exhibited for sounds of a wide frequency, so it is preferable that the dense layer is composed of two or more layers. The more layers that compose the dense layer, the more combinations that compose the pseudo composite layer, and therefore the peak of the vibration frequency increases, but the vibration of multiple layers also interferes, leading to a decrease in the sound absorption characteristics, so the upper limit of the number of layers that compose the dense layer is 10 layers.
[0033] When the dense layer of the laminated structure of the present invention is composed of two or more layers, it is possible to construct the dense layers with different densities as necessary, but considering handleability and vibration as a pseudo-composite layer, it is preferable that the dense layers be of the same structure with the same mechanical properties, etc.
[0034] The dense layer of the laminated structure of the present invention has a total areal density of 150 g / m 2 More than 1500g / m 2 The total surface density here is a value determined by the method described in the Examples below. The total surface density of the dense layer depends on the peak of the vibration frequency of the dense layer, and the higher the total surface density, the lower the peak of the vibration frequency becomes, and high sound absorption properties are exhibited for sounds in the low frequency range. In the present invention, the total surface density of the dense layer is 150 g / m 2 A total surface density of 200 g / m or more is preferable because it fully exhibits sound absorption properties against low-frequency band sounds, particularly sounds of 1000 Hz or less such as road noise. 2 The upper limit of the total surface density at which the low frequency band is fully expressed is 1500 g / m 2Within this range, the vibration frequency of the dense layer becomes low and sound absorption properties are ensured, which is preferable. More preferably, the total surface density is 1000 g / m 2 The following is the result.
[0035] The structure constituting the dense layer of the laminated structure of the present invention has an air permeability of 100 cm 3 / cm 2 The air permeability in the present invention is measured by the method described in the Examples based on the "Air Permeability" A method (Fragile type method) of JIS L1096:2010 "Fabric testing methods for woven and knitted fabrics". 3 / cm 2 By setting the frequency to 50 cm / sec or less, the dense layer vibrates due to the incident sound waves, and the sound absorption characteristics are expressed by resonance with the vibration frequency of the dense layer. 3 / cm 2 More preferably, it is 10 cm / sec or less. 3 / cm 2 / sec or less.
[0036] Examples of the sheet-like material that simultaneously satisfies the above surface density and air permeability include a fiber layer and a microporous membrane, and in particular, a fiber layer that can also exhibit sound absorbing properties as a porous material is preferred. The fiber layer here is a fiber assembly, and examples thereof include nonwoven fabrics, woven fabrics, knitted fabrics, and other fabrics, and nonwoven fabrics are preferred because of the ease of adjusting thickness, surface density, and air permeability. Examples of nonwoven fabrics include spunbond, melt blown, wet papermaking, needle punched felt, electrospun sheets, and the like, and combinations of these may also be used. In particular, as a material that satisfies the characteristics of the above sheet-like material, a nonwoven fabric sheet obtained by wet papermaking is more preferred.
[0037] The base layer of the laminated structure of the present invention has a function of maintaining the shape of the entire laminated structure, and also plays the role of an air layer relative to the dense layer, determining the vibration frequency of the dense layer that exhibits the resonance type sound absorbing characteristics. Materials constituting such a base layer include glass wool, rock wool, foamed foam, and a fiber layer formed by entangling or bonding fibers, and the fiber layer is preferred in terms of moldability, shape stability during use, environmental load during disposal, and the like. The fiber layer here is a fiber assembly, and examples thereof include nonwoven fabrics, woven fabrics, knitted fabrics, and other fabrics, and nonwoven fabrics are preferred in terms of ease of adjusting thickness, surface density, and air permeability. Examples of nonwoven fabrics include spunbond, meltblown, air-through, spunlace, thermal bond, and needle punched felts, and combinations of these may also be used.
[0038] The fibers constituting the base layer of the laminated structure of the present invention are preferably thermoplastic fibers from the viewpoint of the construction of the base layer and waste disposal. The raw materials of the thermoplastic fibers may be those used for general synthetic fibers, for example, aromatic polyesters such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, etc., aliphatic polyesters such as polylactic acid, aliphatic polyamides such as polycapramide and polyhexamethylene adipamide, semi-aromatic polyamides such as polyhexamethylene terephthalamide, thermoplastic elastomers such as thermoplastic polyurethane, polyolefins such as polypropylene, etc.
[0039] The thickness of the base layer of the laminated structure of the present invention is preferably 5 mm or more. As described above, the vibration frequency of the dense layer is determined by the thickness of the base layer. If the thickness is 5 mm or more, the vibration frequency of the dense layer becomes low, and the sound absorption characteristics for the low frequency band of 1000 Hz or less are expressed. In addition, the upper limit of the thickness of the porous layer is about 40 mm in terms of the weight of the laminated structure and the handling during use.
[0040] The substrate layer of the laminated structure of the present invention has an areal density of 100 g / m 2 More than 700g / m 2It is preferable that the surface density is 100 g / m or less. 2 By setting the thickness to the above value, the laminated structure can maintain the shape of the entire structure. In addition, sound absorption properties can be achieved by collision and friction between the incident sound waves and the material constituting the base layer. 2 The surface density is 700 g / m 2 By setting the density to 500 g / m or less, the flexibility of the base material layer can be improved, and the base material layer can play a role as an air layer in the vibration of the dense layer. In addition, since the base material layer has excellent three-dimensional conformability, the shape can be maintained when the laminated structure of the present invention is molded. 2 The following is the result.
[0041] The laminated structure of the present invention exhibits sound absorption characteristics due to the resonance of the vibration frequency of the dense layer with the incident sound wave. Since the sound absorption characteristics are maximized with sound waves that coincide with the frequency at which the vibration of the dense layer is maximized, the sound absorption characteristics are difficult to exhibit due to the transmission or reflection of the incident sound wave except for sounds that coincide with the vibration frequency of the dense layer or sounds close to the vibration frequency of the dense layer. Therefore, in the laminated structure of the present invention, by adjusting the structure of the dense layer as described above, it is possible to selectively absorb sounds of any frequency, and the laminated structure is particularly excellent in sound absorption characteristics in the low frequency band. On the other hand, the above-mentioned transmission or reflection occurs in sounds other than the low frequency band, for example, sounds in the high frequency band exceeding 1000 Hz. Therefore, in order to absorb the transmitted or reflected sounds, it is preferable that the laminated structure of the present invention has a porous layer laminated on the dense layer. A specific example is a structure in which a dense layer is laminated on a base layer, and a porous layer is further laminated on the base layer. The porous layer referred to here is a layer made of a material having a porous structure. In the porous layer, collisions and friction occur between the incident sound waves and the material constituting the porous layer, and the energy of the incident sound waves is converted into thermal energy, and the energy is attenuated to absorb the sound. In addition, the porous layer needs to have a thickness corresponding to the wavelength of the sound to be absorbed, and since high-frequency sounds have short wavelengths and low-frequency sounds have long wavelengths, the higher the frequency of the sound, the better the sound absorption characteristics are. In the laminated structure of the present invention, by laminating the porous layer having the above-mentioned sound absorption mechanism on the dense layer, the sound waves incident on the laminated structure are converted into thermal energy in the porous layer and absorbed, and the low-frequency sound that is difficult to absorb in the porous layer is absorbed by the vibration of the dense layer. Furthermore, since the sound reflected by the dense layer is absorbed by the porous layer, the sound absorption characteristics can be expressed for a wide range of sounds.
[0042] The porous layer used in the laminated structure of the present invention preferably has a thickness of 5 mm or more. As described above, the porous layer needs to have a thickness corresponding to the wavelength of the sound to be absorbed. If the thickness is less than 5 mm, the thickness is insufficient to absorb even high-frequency sounds with short wavelengths, and sound absorption characteristics are not expressed. In addition, the upper limit of the thickness of the porous layer is about 40 mm in terms of the weight of the laminated structure and the ease of handling during use.
[0043] Examples of the porous layer used in the laminated structure of the present invention include glass wool, rock wool, foamed foam, and a fiber layer formed by entangling or bonding fibers, and a fiber layer is preferred in terms of moldability, shape stability during use, and environmental load during disposal. The fiber layer here is a fiber assembly, and examples thereof include nonwoven fabrics, woven fabrics, knitted fabrics, and other fabrics, and a nonwoven fabric is preferred in terms of ease of adjusting thickness, surface density, and air permeability. Examples of nonwoven fabrics include spunbond, meltblown, air-through, spunlace, thermal bond, and needle punched felts, and combinations of these may also be used.
[0044] The fibers constituting the porous layer used in the laminated structure of the present invention are preferably thermoplastic fibers from the viewpoint of manufacturing the porous layer and waste treatment.The raw material of the thermoplastic fibers may be any material used for general synthetic fibers, such as aromatic polyesters represented by polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, etc., aliphatic polyesters represented by polylactic acid, aliphatic polyamides represented by polycapramide and polyhexamethylene adipamide, semi-aromatic polyamides represented by polyhexamethylene terephthalamide, thermoplastic elastomers represented by thermoplastic polyurethane, and polyolefins represented by polypropylene.
[0045] The porous layer used in the laminated structure of the present invention has an air permeability of 1 cm 3 / cm 2 / sec or more 20cm 3 / cm 2 It is preferable that the air permeability of the porous layer is 1 cm 3 / cm 2 If the sound wave is reflected from the surface of the porous layer, the sound wave is prevented from being reflected from the surface of the porous layer, and the sound wave is incident on the laminated structure, and the sound absorbing property is exhibited. 3 / cm 2 / sec or more. Also, the air permeability of the porous layer is 20 cm 3 / cm 2 / sec or less, friction or the like is induced in the porous layer by the incident sound waves, and the energy of the sound waves is efficiently converted into heat energy, resulting in sufficient sound absorption properties. 3 / cm 2 / sec or less can be mentioned as a more preferable range.
[0046] An example of a method for producing the laminated structure of the present invention will be described below.
[0047] As an example of a method for producing a dense layer of the laminated structure of the present invention, a method for producing a sheet-like material by a wet papermaking method will be described. In the wet papermaking method, short fibers constituting the sheet-like material, such as ultrafine fibers, other fibers with a fiber diameter larger than that of ultrafine fibers, and thermally adhesive binder fibers, are put into water and stirred with a disintegrator to prepare a fiber dispersion liquid in which the fibers are uniformly dispersed. In this charging process, it is possible to adjust the dispersibility by the amount of fiber charged, the amount of aqueous medium, the stirring time, etc., and it is preferable that the short fibers are as uniformly dispersed as possible in the aqueous medium. In addition, a post-addition method may be adopted in which an ultrafine fiber dispersion liquid in which the ultrafine fibers are uniformly dispersed in the aqueous medium is separately prepared and mixed with the above-mentioned fiber dispersion liquid.
[0048] An example of a method for producing ultrafine fibers used in the laminated structure of the present invention is to use composite fibers such as multi-layer laminated fibers and sea-island composite fibers, which are made of two or more types of polymers that have different dissolution rates in a solvent. The multi-layer laminated fibers referred to here have a structure in which poorly soluble polymers and easily soluble polymers are laminated alternately or in random order in the cross section, and the laminated structure may be not only one in which the lamination direction in the fiber cross section is the same (FIG. 1), but also one in which the lamination direction is radial, concentric, or irregularly changing, or a combination of these. Furthermore, the sea-island composite fiber has a structure in which island components made of poorly soluble polymers are scattered in a sea component made of easily soluble polymer. By treating this composite fiber in a solvent, the easily soluble polymer is dissolved, and the poorly soluble polymer remains, which becomes the ultrafine fiber.
[0049] The easily soluble polymer in the present invention is selected from, for example, aromatic polyesters such as polyethylene terephthalate, aliphatic polyesters such as polylactic acid, aliphatic polyamides such as polycapramide and polyhexamethylene adipamide, thermoplastic elastomers such as thermoplastic polyurethane, and polyolefins such as polypropylene, which can be melt-formed, and copolymers thereof. In particular, from the viewpoint of simplifying the elution process of the easily soluble polymer, copolymerized polyesters, polylactic acid, polyvinyl alcohol, etc., which are easily soluble in aqueous solvents or hot water, are preferred. Polyesters in which polyethylene glycol and sodium sulfoisophthalic acid are copolymerized alone or in combination are more preferred. From the viewpoints of solubility in aqueous solvents and simplification of waste liquid treatment generated during dissolution, polyesters copolymerized with 3 mol % to 20 mol % of 5-sodium sulfoisophthalic acid and polyesters copolymerized with 3 mol % to 20 mol % of 5-sodium sulfoisophthalic acid and 5 wt % to 15 wt % of polyethylene glycol having a weight average molecular weight of 500 to 3,000 are particularly preferred.
[0050] As a method for producing the composite fiber, a method using melt spinning with a composite spinneret is preferred because it is excellent in productivity, and in control of fiber diameter and cross-sectional shape. When using the melt spinning method, the spinning temperature is set to a temperature at which the polymers used, mainly those with high melting points or high viscosity, exhibit fluidity. The temperature at which this fluidity is exhibited varies depending on the molecular weight, but stable production is possible when it is set between the melting point of the polymer and melting point + 60°C.
[0051] In the melt spinning method, for example, a soluble polymer and a poorly soluble polymer are melted separately, metered and transported by a gear pump, and a composite flow is formed by a known method so as to have a specific composite structure, which is then discharged from a spinneret. At this time, it is preferable to set the melt viscosity ratio of the two polymers (polymer with high melt viscosity / polymer with low melt viscosity) to less than 5.0, since this allows a stable formation of a composite polymer flow and allows the production of fibers with a good composite cross section.
[0052] Next, the yarn discharged from the spinneret is cooled to room temperature by blowing cooling air using a yarn cooling device such as a chimney, and is oiled and focused using an oiling device. The focused yarn is entangled using a fluid entanglement nozzle device and passed through a take-up roller and a stretching roller. At this time, it is stretched according to the ratio of the peripheral speeds of the take-up roller and the stretching roller. Further, the yarn is heat-set using a stretching roller and wound up using a winder (winding device). Another example is a two-step method in which the peripheral speeds of the take-up roller and the stretching roller are set to the same speed, and the yarn is wound up using a winder that also has the same speed to form an unstretched yarn, which is then stretched in a separate step.
[0053] Next, the composite fibers obtained by the above manufacturing method are bundled into a tow of several tens to several millions of fibers, and are cut to the desired fiber length using a cutting machine such as a guillotine cutter, a slicer, or a cryostat to obtain short composite fibers.
[0054] Furthermore, the obtained short fibers of the composite fiber are treated with a solvent capable of dissolving the easily soluble polymer to remove the easily soluble polymer, thereby obtaining ultrafine fibers made of a hardly soluble polymer. For example, when the easily soluble polymer is a copolymer polyester in which 5-sodium sulfoisophthalic acid or polyethylene glycol is copolymerized, the solvent used in this treatment is preferably an aqueous solution containing an alkali such as sodium hydroxide as a solute. In this case, the bath ratio of the composite fiber to the alkaline aqueous solution (weight of the composite fiber / weight of the alkaline aqueous solution) is preferably 1 / 10000 or more and 1 / 5 or less. By setting the bath ratio in this range, it is possible to suppress entanglement of the ultrafine fibers when dissolving and removing the easily soluble polymer. In addition, the alkaline concentration of the alkaline aqueous solution is preferably 0.1% by weight or more and 5% by weight or less. By setting the alkaline concentration in this range, it is possible to complete dissolution of the easily soluble polymer in a short time, and to suppress deterioration of the hardly soluble polymer. Furthermore, by setting the temperature of the alkaline aqueous solution during the dissolution treatment to 50° C. or more, it is possible to accelerate the progress of dissolution of the easily soluble polymer.
[0055] The cross-sectional shape of the ultrafine fibers in the laminated structure of the present invention can be not only round, but also a wide variety of cross-sectional shapes such as flat, Y-shaped, T-shaped, hollow, square, well-shaped, etc. The cross-sectional shape can be adjusted when forming a composite flow in a spinneret so as to have a specific composite structure.
[0056] When the short ultrafine fibers obtained by the above method are used in a wet papermaking process, the post-treatment liquid obtained by dissolving the easily soluble polymer from the composite fibers may be used as an ultrafine fiber dispersion liquid. Alternatively, the post-treatment liquid may be filtered to separate the ultrafine fibers, washed with water, and dried to form a clay-like material, which may then be added to the fiber dispersion liquid as a raw material.
[0057] When preparing the fiber dispersion, a dispersant may be added to improve the dispersibility of each fiber in water. As the type of dispersant, for example, additives for suppressing the aggregation of fibers include cationic compounds, anionic compounds, and nonionic compounds. In particular, it is preferable to use anionic compounds from the viewpoint of electrical repulsion in an aqueous medium. The amount of these dispersants to be added is preferably 0.001 to 10 equivalents relative to the weight of the ultrafine fibers in order to ensure dispersibility without impairing processability during wet papermaking.
[0058] Examples of equipment used in wet papermaking include a cylinder papermaking machine, a fourdrinier papermaking machine, an inclined short wire papermaking machine, or a combination of these. In the papermaking process, the fiber dispersion prepared as described above is diluted to a certain concentration, and then dehydrated on an inclined wire or a cylinder to form a wet papermaking sheet. At this time, a three-dimensionally homogeneous sheet can be produced by controlling the accumulation of fibers during filtration by adjusting the papermaking speed, fiber amount, and aqueous medium amount in addition to the dispersibility of fibers in the papermaking stock. In addition, the areal density and thickness of the wet papermaking sheet can be adjusted by appropriately changing the supply amount of the fiber dispersion, which is the papermaking stock, and the papermaking speed.
[0059] Next, the formed wetlaid paper sheet is dried to remove moisture. Drying methods include a method of passing hot air through (air through) and a method of contacting with a heated rotating roll (heated calendar roll, etc.) because the sheet can be thermally bonded at the same time as drying the sheet and the sheet contains binder fibers.
[0060] The mode of laminating two or more layers in the dense layer of the laminated structure of the present invention can be adjusted appropriately. Examples include a method of simply stacking multiple wetlaid paper sheets, a method of melting binder fibers contained in the wetlaid paper sheets, or a method of bonding multiple wetlaid paper sheets via a binder agent. The bonding mode of multiple wetlaid paper sheets via a binder agent can also be appropriately selected, and examples include a mode in which a low-melting point polymer is applied in a dot shape and bonded, a mode in which the sheets are bonded using a spider web-shaped (web-shaped) low-melting point polymer sheet (thermal bonding sheet), and a mode in which the laminated multiple wetlaid paper sheets are bonded by impregnating them with a binder agent solution and drying them.
[0061] The manufacturing method of the base layer of the laminated structure of the present invention can be exemplified by the following method. First, the short fibers constituting the base layer are weighed. At this time, the type of short fibers may be one type or two or more types, but it is preferable to include binder fibers in order to maintain the shape of the base layer. The weighed short fibers are sufficiently opened and mixed using air or the like, and the mixed short fibers are aligned with a clothed roller to obtain a mixed fiber web. Next, the mixed fiber web is heat-treated with a hot air dryer, a hot air circulation type heat treatment machine, an infrared heater, a heat roll, or the like at a temperature higher than the temperature at which the binder fibers soften or melt, to obtain a nonwoven fabric that will become the base layer. In addition, when binder fibers are not used, the short fibers may be entangled by a mechanical entanglement method using needles or a water flow.
[0062] As an example of a method for manufacturing the porous layer of the laminated structure of the present invention, a manufacturing method by melt blowing is shown below. First, the thermoplastic resin that is the raw material of the nonwoven fabric is melted and supplied to a die, and hot air is blown onto the yarn extruded from the die to thin the nonwoven fibers. Short fibers made of a thermoplastic resin and binder fibers are blown onto the fiber flow of the nonwoven fibers so that they merge, and collected on a net as a mixed web. At this time, the thermoplastic resin that is the raw material of the nonwoven fabric and the thermoplastic resin that constitutes the short fibers and binder fibers may be the same polymer or different types of polymers. Next, the mixed web is heat-treated at a temperature higher than the temperature at which the binder fibers soften or melt using a hot air dryer, a hot air circulation type heat treatment machine, an infrared heater, a heat roll, or the like, to obtain a nonwoven fabric that will become a porous layer. In addition, when binder fibers are not used, each fiber may be entangled by a mechanical entanglement method using needles or water flow. Furthermore, the mixed web may be shaped such that another nonwoven fabric is bonded to it as a cover material via a thermally adhesive binder agent.
[0063] The mode of laminating the dense layer and the base layer, and the mode of laminating the porous layer and the dense layer to obtain the laminated structure of the present invention can be appropriately adjusted. Examples include a method of simply laminating the dense layer and the base layer, and the porous layer and the dense layer, a method of melting the binder fibers contained in the porous layer and / or the dense layer and / or the base layer, and a method of bonding the dense layer and the base layer, and the porous layer and the dense layer through a binder agent. The adhesion mode of the dense layer and the base layer through the binder agent, and the adhesion mode of the porous layer and the dense layer can also be appropriately selected. Examples include a mode in which a low-melting point polymer is applied in a dot shape and bonded, a mode in which the layers are bonded by a spider web-like (web-like) low-melting point polymer sheet, and a mode in which the laminated dense layer and the base layer, and the porous layer and the dense layer are bonded by impregnating them with a binder agent solution and drying them. The lamination of the dense layer and the base layer and the lamination of the porous layer and the dense layer may be performed in separate steps or in the same step.
[0064] The laminated structure of the present invention may be subjected to known treatments such as dyeing, nap raising, water repellency, flame retardancy, and the like.
[0065] The shape of the laminated structure of the present invention can be appropriately adjusted, and may be, for example, a round shape, an oval shape, a square shape, a rectangular shape, etc. Also, the laminated structure may be corrugated, pleated, wound, cut, punched, or perforated, or may have a partially notched shape.
[0066] The laminated structure of the present invention can be used as a sound absorbing material in various applications such as automobiles, electronic devices, buildings, and homes. The method of use as a sound absorbing material can be appropriately selected according to the application, such as pasting on a wall surface or inside a device, or filling inside a wall. In particular, the sound absorbing material made of the laminated structure of the present invention has excellent sound absorbing properties in the low frequency band, and is suitable for noise countermeasures in the low frequency band of 1000 Hz or less, such as road noise, when used as a part of a sound absorbing part for a vehicle. EXAMPLES
[0067] The present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. The respective property values in the examples were measured by the following methods.
[0068] A. Fiber diameter The dense layer was embedded in an embedding agent such as epoxy resin, frozen using a Reichert FC-4E cryosectioning system, cut using a Reichert-Nissei ultracut N (ultramicrotome) equipped with a diamond knife, and the cut surface was photographed using a Hitachi H-7100FA transmission electron microscope (TEM) at a magnification that allowed the cross section to be recognized. One hundred fibers were randomly extracted from the photograph, and the diameters of the single fibers were measured using image analysis software (WINROOF), and the average of the 100 fibers was calculated. The arithmetic average was rounded off to the nearest whole number to obtain the fiber diameter (nm). In addition, when the fiber cross section was not a perfect circle, the maximum length of the cross section of the single fiber was measured, and the length at which the line segment perpendicular to the maximum length at the midpoint of the maximum length intersected the fiber cross section was calculated as the fiber diameter.
[0069] B. Flatness For 100 fibers extracted from the photograph obtained in A above, the maximum length of the cross section of the single fiber was measured, and the average value was calculated as the long axis length of the single fiber by rounding off to the nearest integer in nm. Next, the length of the line segment perpendicular to the line segment of the maximum length at the midpoint of the maximum length intersecting the fiber cross section was measured, and the average value was calculated as the short axis length of the single fiber by rounding off to the nearest integer in nm. Using these long axis length and short axis length, the following formula was used: Flatness = Length along the major axis (nm) / Length along the minor axis (nm) The flatness of the single fiber was calculated by the above.
[0070] C. Fiber length The surface of the dense layer was photographed with a microscope at a magnification that allowed observation of 10 to 100 fibers whose full length could be measured. The fiber length of 10 fibers randomly extracted from each photographed image was measured. The fiber length referred to here is the length of one fiber in the longitudinal direction from a two-dimensionally photographed image, measured in mm to three decimal places, and rounded off to the nearest tenth. The above operation was carried out for 10 similarly photographed images, and the simple number average of the evaluation results of the 10 images was taken as the fiber length.
[0071] D. Fiber orientation angle The photograph obtained in A above was arranged so that the top and bottom directions were the top and bottom of the dense layer, and 100 fibers were randomly selected. The fiber orientation angle of the single fibers was measured using image analysis software (WINROOF), and the average value of the 100 fibers was calculated. The arithmetic average was rounded off to the nearest whole number to obtain the fiber orientation angle (°). If the single fiber was bent, the fiber orientation angle of the part with the longest straight line distance in the photograph was measured, and this value was used as the orientation angle of the single fiber. In addition, the squares of the deviations, which are the differences between the fiber orientation angles of the 100 fibers and the average value, were summed up, and the positive square root was used as the standard deviation, after dividing by 100, the number of fibers measured.
[0072] E. Areal density (total areal density) The weight of the sample cut into a 250 mm × 250 mm square was measured and the unit area (1 m 2The surface density (total surface density) was calculated by rounding off the converted weight per unit area to an integer.
[0073] F. Thickness The thickness was measured in mm using a dial thickness gauge (TECLOCK SM-114, probe shape 10 mmφ, graduation 0.01 mm, measuring force 2.5 N or less). Measurements were taken at five random locations per sample, and the average was rounded off to two decimal places to determine the thickness.
[0074] G. Breathability According to the method described in JIS L1913 (2010), the air permeability of the sample was measured using a Frazier type tester, and the value obtained by rounding off to the first decimal place was regarded as the air permeability. 3 / cm 2 / sec, <0.5cm 3 / cm 2 It is expressed as / sec.
[0075] H. Sound absorption coefficient A circular test piece with a diameter of 39.5 mm was taken from the sample, and the sound absorption coefficient was measured from 100 to 5000 Hz in accordance with JIS A1405 (2007) "Measurement of sound absorption coefficient and impedance using an acoustic tube." The sound absorption coefficient (%) was evaluated at 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz.
[0076] I. Transmission loss A circular test piece with a diameter of 41.5 mm was taken from the sample, and the normal incidence transmission loss was measured at 100 to 5000 Hz in accordance with ASTM E2611. The transmission loss (dB) was evaluated at 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz.
[0077] Example 1 Polyethylene terephthalate (melt viscosity 160 Pa s, melting point 254 °C) was used as component A, and polyethylene terephthalate (melt viscosity 121 Pa s, melting point 234 °C) copolymerized with 8.0 mol% 5-sodium sulfoisophthalic acid and 10 mass% polyethylene glycol with a number average molecular weight of 1000 was used as component B. After melting components A and B separately at 290 °C, the components were fed into a spinning pack equipped with a composite spinneret using a composite plate capable of laminating both components alternately in 36 layers at a composite ratio of 80 / 20, and a composite polymer stream was discharged from the discharge hole so as to form a composite form in which two types of polymers were alternately laminated in multiple layers in one direction, as shown in Figure 1. The discharged composite polymer stream was cooled and solidified, and then oil was applied, and the stream was wound at a spinning speed of 1000 m / min, and an undrawn yarn of 200 dtex-48 filaments (total discharge rate 20 g / min) was obtained. The wound undrawn fiber was drawn 3.6 times between rollers heated to 90° C. and 130° C. to obtain a drawn fiber of 56 dtex-48 filaments.
[0078] The obtained multilayer laminated fiber was cut to a fiber length of 3.0 mm, and the cut multilayer laminated fiber was immersed in a 1 wt% sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 90°C for 30 minutes, thereby dissolving and removing more than 99% of the easily soluble polymer SSIA-PEG copolymerized PET, and obtaining short fibers with a flat cross-section as shown in Figure 2.
[0079] Next, the obtained flat short fibers were charged into a disintegrator together with water so that the content was 40% by mass, 30% by mass of short fibers (core component fiber diameter 10 μm, fiber length 5.0 mm) of thermally adhesive core-sheath composite fibers (sheath component: low melting point polyethylene terephthalate (melting point 110°C), core component: polyethylene terephthalate (melting point 255°C)) as binder fibers (core component fiber diameter 10 μm, fiber length 5.0 mm), and 30% by mass of polyethylene terephthalate short fibers (fiber diameter 4 μm, fiber length 3.0 mm), and the mixture was uniformly mixed and dispersed to obtain a papermaking stock solution. This papermaking stock solution was made into paper using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and then dried and heat-treated in a rotary dryer with a roller temperature set at 110°C, until the surface density reached 100 g / m 2 A wet-laid paper sheet of 100 g was obtained.
[0080] Next, 50% by mass of polyethylene terephthalate staple fibers (fiber diameter 20 μm, fiber length 51 mm), 15% by mass of polyethylene terephthalate staple fibers with a hollow cross section (hollowness 50%, fiber diameter 38 μm, fiber length 51 mm), 20% by mass of polyethylene terephthalate staple fibers (fiber diameter 12 μm, fiber length 35 mm), and 15% by mass of thermally adhesive core-sheath composite fibers (sheath component: low melting point polyethylene terephthalate (melting point 110°C), core component: polyethylene terephthalate (melting point 255°C)) staple fibers (core component fiber diameter 10 μm, fiber length 51 mm). Next, the fibers were mixed and opened using a carding machine to form a uniform web. The formed web is laminated to a specified thickness, and while pressing the web to a thickness of 20 mm with a press roll, the fibers are heat-sealed in a heat treatment furnace equipped with upper and lower net conveyors at 215°C to produce a surface density of 250 g / m 2 The thickness was adjusted to 20 mm to obtain a nonwoven fabric.
[0081] In preparing the laminated structure, three sheets of the wet-laid paper sheets prepared above were stacked as they were to form a dense layer, and the nonwoven fabric was used as the base layer. First, one thermal adhesive sheet was placed on the nonwoven fabric coming out of the heating furnace, and three sheets of the wet-laid paper sheets were stacked on top of it. The entire structure was pressed with a 130°C heating roller to melt the thermal adhesive sheet, bonding the wet-laid paper sheets and the nonwoven fabric layer, and obtaining a laminated structure. Circular samples with diameters of 39.5 mm and 41.5 mm were cut out from the obtained laminated structure and evaluated as sound-absorbing materials. The evaluation results are shown in Table 1.
[0082] Comparative Example 1 A laminated structure was produced in the same manner as in Example 1, except that when making the wetlaid paper sheet, the water flow was adjusted so that the orientation angle of the ultrafine fibers was as shown in Table 1, and the laminated structure was evaluated as a sound absorbing material. The evaluation results are shown in Table 1. Because the orientation angle was high at 60°, the sound absorbing performance was poor.
[0083] (Examples 2 and 3) A laminated structure was produced in the same manner as in Example 1, except that the mixing ratio of each fiber was adjusted to be as shown in Table 1 when making the wetlaid paper sheet, and was evaluated as a sound absorbing material. The evaluation results are shown in Table 1. As the mixing ratio of component fiber 1 increased, the air permeability of the dense layer decreased and the transmission loss increased.
[0084] Example 4 Polyethylene terephthalate (melt viscosity 160 Pa s, melting point 254 °C) was used as component A, and polyethylene terephthalate (melt viscosity 121 Pa s, melting point 234 °C) copolymerized with 8.0 mol% 5-sodium sulfoisophthalic acid and 10 mass% polyethylene glycol with a number average molecular weight of 1000 was used as component B. After melting components A and B separately at 290 °C, the components were fed into a spinning pack equipped with a composite spinneret using a composite plate capable of laminating both components alternately in 36 layers at a composite ratio of 80 / 20, and a composite polymer stream was discharged from the discharge hole so as to form a composite form in which two types of polymers were alternately laminated in multiple layers in one direction, as shown in Figure 1. The discharged composite polymer stream was cooled and solidified, and then oil was applied, and the stream was wound at a spinning speed of 1000 m / min, and an undrawn yarn of 200 dtex-48 filaments (total discharge rate 20 g / min) was obtained.
[0085] The obtained multi-layer laminated fiber was cut to a fiber length of 5.0 mm, and the cut multi-layer laminated fiber was immersed in a 1 wt % sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 50°C for 60 minutes to obtain short fibers with a flat cross section. A laminated structure was produced in the same manner as in Example 1, except that the short fibers were used as binder fibers, and evaluated as a sound absorbing material. The evaluation results are shown in Table 1.
[0086] Example 5 A laminated structure was produced in the same manner as in Example 1, except that the flatness of component fiber 1 was changed to be as shown in Table 1, and evaluated as a sound absorbing material. The evaluation results are shown in Table 1.
[0087] (Example 6, Comparative Example 2) A laminated structure was produced in the same manner as in Example 1, except that the fiber diameter of component fiber 1 was changed as shown in Table 1, and evaluated as a sound absorbing material. The evaluation results are shown in Table 1.
[0088] (Examples 7 to 10) A laminated structure was produced in the same manner as in Example 1, except that the surface density and number of layers of the sheet-like material constituting the dense layer were changed as shown in Table 2, and evaluated as a sound absorbing material. The evaluation results are shown in Table 2.
[0089] Example 11 Polyethylene terephthalate (melt viscosity 160 Pa s, melting point 254°C) was used as the island component, and polyethylene terephthalate copolymerized with 8.0 mol% 5-sodium sulfoisophthalic acid and 10 mass% polyethylene glycol with a number average molecular weight of 1000 (melt viscosity 121 Pa s, melting point 234°C) was used as the sea component. After melting each component separately at 290°C, the composite ratio of the islands / sea components was set to 50 / 50, and the inlet polymer was discharged from the discharge hole into a spin pack equipped with a sea-island composite spinneret (2000 islands) with round island components. The discharged composite polymer stream was cooled and solidified, and then an oil agent was added. The first roll, the take-up roller, was then taken up at a peripheral speed of 1000 m / min and a temperature of 85°C. The yarn taken up by the take-up roller was then taken up by a second roll, the stretching roller, with a surface temperature of 130° C., to be stretched at a draw ratio of 3.4 times, which is expressed as the ratio of the peripheral speeds of the take-up roller and the stretching roller, and was simultaneously heat-treated by the stretching roller. The heat-treated yarn was wound up by a winder with a winding speed of 3400 m / min, to obtain a drawn yarn of 100 dtex-14 filament.
[0090] The obtained drawn yarn was cut to a fiber length of 0.6 mm. The cut drawn yarn was then placed in an aqueous sodium hydroxide solution (concentration: 1% by mass) with a mass 100 times that of the drawn yarn, and heated at 90° C. to obtain an ultrafine fiber dispersion.
[0091] Next, short fibers (core component fiber diameter 10 μm, fiber length 5.0 mm) of heat-fusible core-sheath composite fibers (sheath component: low-melting point polyethylene terephthalate (melting point 110°C), core component: polyethylene terephthalate (melting point 255°C)), short fibers of polyethylene terephthalate (fiber diameter 4 μm, fiber length 3.0 mm) and water were added to a disintegrator and mixed and dispersed uniformly to obtain a fiber dispersion.
[0092] Furthermore, the fiber dispersion and ultrafine fiber dispersion were homogeneously mixed to prepare a papermaking stock solution containing 30% by mass of heat-fusible core-sheath composite fibers, 65% by mass of polyethylene terephthalate short fibers, and 5% by mass of ultrafine fibers. This papermaking stock solution was made into paper using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and then dried and heat-treated in a rotary dryer with a roller temperature set at 110°C to obtain a surface density of 100 g / m 2 A wet-laid paper sheet of 100 g was obtained.
[0093] Next, 50% by mass of polyethylene terephthalate staple fibers (fiber diameter 20 μm, fiber length 51 mm), 15% by mass of polyethylene terephthalate staple fibers with a hollow cross section (hollowness 50%, fiber diameter 38 μm, fiber length 51 mm), 20% by mass of polyethylene terephthalate staple fibers (fiber diameter 12 μm, fiber length 35 mm), and 15% by mass of thermally adhesive core-sheath composite fibers (sheath component: low melting point polyethylene terephthalate (melting point 110°C), core component: polyethylene terephthalate (melting point 255°C)) staple fibers (core component fiber diameter 10 μm, fiber length 51 mm). Next, the fibers were mixed and opened using a carding machine to form a uniform web. The formed web is laminated to a specified thickness, and while pressing the web to a thickness of 20 mm with a press roll, the fibers are heat-sealed in a heat treatment furnace equipped with upper and lower net conveyors at 215°C to produce a surface density of 250 g / m 2 The thickness was adjusted to 20 mm to obtain a nonwoven fabric.
[0094] In preparing the laminated structure, three sheets of the wet-laid paper sheets prepared above were stacked as they were to form a dense layer, and the nonwoven fabric was used as the base layer. First, one thermal adhesive sheet was placed on the nonwoven fabric coming out of the heating furnace, and three sheets of the wet-laid paper sheets were stacked on top of it. The entire structure was pressed with a 130°C heating roller to melt the thermal adhesive sheet, bonding the wet-laid paper sheets and the nonwoven fabric layer, and a laminated structure was obtained. Circular samples with diameters of 39.5 mm and 41.5 mm were cut out from the obtained laminated structure and evaluated as sound-absorbing materials. The evaluation results are shown in Table 2.
[0095] Comparative Example 3 The nonwoven fabric produced in Example 1 was evaluated as a sound absorbing material. The evaluation results are shown in Table 2. Since there was no dense layer, the sound absorbing properties were poor in the low frequency band of 1000 Hz or less, and the transmission loss was also poor.
[0096] Example 12 A laminated structure was produced in the same manner as in Example 1, except that a melt-blown nonwoven fabric (manufactured by 3M, product name: TC1503) made of polypropylene resin was laminated as a porous layer on the wet-laid paper sheet side of the laminate of the wet-laid paper sheet and nonwoven fabric produced in Example 1, and evaluated as a sound absorbing material. The evaluation results are shown in Table 3.
[0097] (Examples 13 and 14) Except for changing the laminate used in Example 12 to Example 2 in Example 13 and to Example 3 in Example 14, a laminate structure was produced in the same manner as in Example 12 and evaluated as a sound absorbing material. The evaluation results are shown in Table 3. The mixing ratio of component fiber 1 in the dense layer increased, the transmission loss increased, and the sound absorbing performance improved.
[0098] Comparative Example 4 A laminate structure was produced in the same manner as in Example 11, except that the laminate used in Example 12 was changed to only the nonwoven fabric produced in Example 1, and evaluated as a sound absorbing material. The evaluation results are shown in Table 3.
[0099] [Table 1]
[0100] [Table 2]
[0101] [Table 3] [Explanation of symbols]
[0102] AA component BB ingredient C Short Fiber
Claims
1. A laminated structure in which a dense layer is laminated on a base layer, the dense layer having at least ultrafine fibers with a fiber diameter of 100 to 1000 nm, and a fiber orientation angle of the ultrafine fibers with respect to a planar direction of the dense layer is 0 to 45°.
2. 2. The laminated structure according to claim 1, characterized in that at least one type of fiber constituting the dense layer has a flatness, which is the value obtained by dividing the length of the long axis of a fiber cross section by the length of the short axis, of 5 or more and an average length of the short axis of 1000 nm or less.
3. 3. The laminated structure according to claim 1, wherein the dense layer is made of thermoplastic fibers.
4. The dense layer has a total areal density of 150 g / m 2 More than 1500g / m 2 3. The laminate structure according to claim 1, wherein:
5. 3. The laminated structure according to claim 1, wherein a porous layer is laminated on the dense layer.
Citation Information
Patent Citations
Sound absorber
JP2015121631A
Sound absorbing felt
JP2017037173A
Laminate sound absorbing material
JP2020019251A